Media Lokal dalam Proses Demokratisasi: Agen Politik atau Saluran Komunikasi Politik? - Syahrul Hidayanto Yanto; Wahyu Hamdani Haerudin; Guntur Freddy Prisanto; Niken Febrina Ernungtyas (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2020)
The issue of neutrality and professionalism is still attached to the local media. On the one hand, many local media claim to position themselves as channels of political communication. However, on the other hand, the local media are suspected of being political agents of regional leaders. This study aims to describe the position of local media in the democratization process. The paradigm used in this research is constructivism with a qualitative – dialectical approach. Data collection techniques are in – depth interviews, observation, and literature study. There were four informants consisting of two local politicians and two local media editors. The research data were analyzed using thematic analysis. The results showed that the positioning of the local media as a channel of political communication for local political elites was still strong. Elements of proximity and local values ​​make local media still exist. Then, of the four interests that influence media content, economic and political interests still dominate. Local media also have not fulfilled all the requirements for the creation of a pro-democracy media system. The conditions that are not met are tight supervision of the government, guaranteeing protection for weak groups, and the ability to represent group interests. Keywords : Democracy; Local Media; Media Agenda; Political Actor; Political Communication